2007
DOI: 10.1002/icd.506
|View full text |Cite
|
Sign up to set email alerts
|

Wobbles, humps and sudden jumps: a case study of continuity, discontinuity and variability in early language development

Abstract: Current individual-based, process-oriented approaches (dynamic systems theory and the microgenetic perspective) have led to an increase of variability-centred studies in the literature. The aim of this article is to propose a technique that incorporates variability in the analysis of the shape of developmental change. This approach is illustrated by the analysis of time serial language data, in particular data on the development of preposition use, collected from four participants. Visual inspection suggests t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 38 publications
2
65
0
2
Order By: Relevance
“…For instance, the techniques proposed by van Dijk and van Geert (2007) and Harezlak and Heckman (1999) can identify spurts, but not where they occur, how large they are, and how long they last. The technique used by Molinari et al (1980) allows identification of the time when the spurt is most intense (similar to the point of maximal velocity in AMD) and the velocity at that point.…”
Section: Strengths Of the Amd Methodsmentioning
confidence: 99%
“…For instance, the techniques proposed by van Dijk and van Geert (2007) and Harezlak and Heckman (1999) can identify spurts, but not where they occur, how large they are, and how long they last. The technique used by Molinari et al (1980) allows identification of the time when the spurt is most intense (similar to the point of maximal velocity in AMD) and the velocity at that point.…”
Section: Strengths Of the Amd Methodsmentioning
confidence: 99%
“…Studies in several topics have shown evidence of nonlinearity, for instance, in language (e.g. van Dijk & van Geert, 2007), interaction behaviors (e.g. Hollenstein, Granic, Stoolmiller, & Snyder, 2004) and scientific reasoning (e.g.…”
Section: A Emergência Do Planejamento Cognitivo a Curto Prazo: Desempmentioning
confidence: 99%
“…La variabilidad ha jugado un papel que ha oscilado entre la incomodidad y la promesa de ser la clave para entender el desarrollo (Miller, 2002;Puche-Navarro, 2003, 2008Siegler, 1995Siegler, , 2002aSiegler & Svetina, 2002van Dijk & van Geert, 2007;Yan & Fischer, 2002). La relación entre la variabilidad y procesos construcción del conocimiento, se consolida "como distintos itinerarios para acceder al conocimiento" (Rose & Fischer, 2009, p. 400).…”
Section: El Problema De La Variabilidadunclassified